Chemical reaction on hydromagnetic natural convective flow over an unlimited perpendicular permeable plate. Issue 7 (30th May 2022) - Gopal, Ch. H. K.; Sudhakar, M.; Masthan Rao, S.
Abstract: In this paper, we have explored the hydromagnetic free convective flow over an unlimited perpendicular porous plate in the presence of temperature resources. The prevailing equations are subsequently solved systematically by utilizing the perturbation methodology. The velocity, temperature as well as concentration sketches are shown in graphical profiles. The impacts in the flow area for dissimilar leading parameters have been explored. Also, the skin frictions, the Nusselt quantity along with the Sherwood quantity are computed with different parameters and mentioned in the tables. The velocity diminishes with an escalation in the chemically reacting parameter as well as improves with an increment in the temperature resource parameter. The temperature field reduces with an augment in the Prandtl number. The concentration field is enhanced by amplifying in the chemically reacting variable, whereas it lessens with amplifying in the Schmidt number.